GERAKAN ANAK HEBAT DENGAN EDUKASI HAND HYGIENE DAN JAJANAN SEHAT - Dyah Rahmawatie Ratna Budi Utami; Siti Fatmawati (P3M Universitas Aisyiyah Surakarta, 2017)
Great kids need to have healthy behaviors. Instinctively children love snack and more interested in snacks with various color and taste. Ironically these days children's snacks become a problem that needs the attention of the public, because the snacks are at risk of contamination by biological or chemical contaminants that can interfere with health, both short and long term. The purpose of community service is to improve the knowledge and skills in hand washing and choosing healthy snacks. This devotional activity is conducted one day in the form of an interactive discussion with the material about choosing healthy snacks, demonstrations and redemontration handwashing way. Based on observations during community service activities, some positive results were obtained, such as: 1). The participants are enthusiastic about the material 2). The participants were active in the question and answer session and half more enthusiastic participants demonstrated hand washing. The result is the improvement of knowledge and skill of participants related to choosing healthy snacks and hand washing. The conclusion of this activity is education with interactive discussion, demonstration and redemonstration able to improve the knowledge and skill of children about hand washing and choosing healthy snacks.